Islamic Role of Bystander in Domestic Violence Prevention (Lembaga Contrarius Indonesia, 2026)
Domestic violence is a pervasive global issue cutting across ethnic, social and religious background, leaving behind serious social, psychological, and economic trauma in its victims, combating domestic violence (DV) is therefore, very crucial to human and societal development. This article aims to examines fighting domestic violence within the context of Islamic teachings, focusing on the religious, moral and legal obligations of bystanders. Using a qualitative approach, the study explores the fundamental sources of Islamic law; Quran, Prophetic traditions, and Islamic jurisprudential principles. The study examines the Islamic principle of Amr bil Ma’ruf wa Nahi anil Munkar (enjoining good and forbidding evil) as one of the fundamental principles of Islam which places both moral and religious obligation on bystander to intervene and protect the vulnerable in the face of aggression, hence, serves as contribution to the global fight against domestic violence particularly relevant for policymakers, scholars, and religious leaders.